Migraine in gulf war illness and chronic fatigue syndrome: prevalence, potential mechanisms, and evaluation - Rayhan, Rakib; Ravindran, Murugan K.; Baraniuk, James N. (Frontiers in Physiology, 2013)
Objective: To assess the prevalence of headache subtypes in Gulf War Illness and Chronic Fatigue Syndrome compared to controls. Background: Migraines are reported in Chronic Fatigue Syndrome (CFS). Approximately, 25% of the military personnel who served in the 1990-1991 Persian Gulf War have developed Gulf War Illness (GWI). Symptoms in GWI share considerable overlap with CFS, including headache complaints. The type and prevalence of headaches in GWI have not been adequately assessed. Methods: 50 GWI, 39 CFS and 45 controls were examined. Participants had structured headache evaluations based on the 2004 International Headache Society criteria. All subjects had history and physical examinations, measurements of systemic hyperalgesia (dolorimetry), assessments for exclusionary indicators, fatigue and symptom related questionnaires. Results: Migraines were detected in 64% of GWI (odds ratio, 11.6, [±95% CI, 4.1 to 32.5]) and 82% of CFS subjects (odds ratio, 22.5, [±95% CI, 7.8 to 64.8]) compared to only 13% of controls. There was a predominance of females in the CFS compared to GWI and controls. However, gender did not influence migraine status (x2= 2.7; P = 0.101). Measures of fatigue, pain, and other ancillary criteria were comparable between GWI and CFS subjects with and without headache. Conclusion: Results validate previous findings of migraine in CFS and confirms similar increased prevalence in GWI compared to controls. This suggests GWI and CFS subjects share pathophysiological mechanisms that underlie migraine attacks and contribute to the extensive overlap of symptom constructs and disease pathophysiology. The high migraine prevalence warrants the inclusion of a structured headache evaluation that coincides with clinical assessments of GWI and CFS diagnosis.